Joint Impact Assessment of CTA's support to RUFORUM (2003-2013) - Obua-Ogwal, Agnes Akwang; Kayobyo, Godfrey (Technical Centre for Agricultural and Rural Cooperation, 2020)
The Regional Universities Forum for Capacity Building in Agriculture (RUFORUM) established in 2004 is a consortium of 32 member universities in 18 countries in Eastern, Central and Southern Africa (ECSA). RUFORUM’s mandate is to oversee graduate training and networks in the region. RUFORUM and the Technical Center for Agricultural and Rural Cooperation (CTA), have collaborated over the last 10 years during which they have undertaken several partnership activities.